A customer-oriented manager for B2B services - Mathieu, Valérie (Innovation, entrepreneurship and management series., 2022)
The notion of customer orientation is becoming a necessity rather than a choice for many companies. It is a lasting response to competitive pressure and supports the company in a renewed definition of its mission, beyond direct economic gain. Within B2B services, the manager, through proximity to their team, their market and their client, is the essential actor in the deployment of this orientation. A Customer-oriented Manager for B2B Services provides managers with the knowledge and tools necessary to implement customer orientation themselves, with the involvement of their extended team. To this end, this book presents a four-step approach: understand the fundamentals of customer orientation in B2B services, know the customer, make the most of the offer and deliver the service.